Conceptual Approach to Forming the Basic Code of Neo-Industrial Development of a Region - Andreeva, E.L.; Karkh, D.A.; Myslyakova, Yu.G. (Economy of Regions, 2017)
In the article, the authors propose the conceptual fundamentals of the “code approach” to the regional neo-industrial development. The purpose of the research is to reveal the essence of the transition to a new type of industrial and economic relations through a prism of “genetic codes” of the region. We consider these codes as a system of the "racial memory” of a territory, which determines the specificity and features of neo-industrialization realization. We substantiated the hypothesis about the influence of the “genetic codes” of the region on the effectiveness of the neo-industrialization. We have defined the participants, or else the carriers of the codes in the transformation of regional inheritance for the stimulation of the neoindustrial development of regions economy. The subject matter of the research is the distinctive features of the functioning of the determinative regions codes. Their content determines the socio-economic specificity of the region and the features of innovative, informational, value-based and competence-based development of the territory. The determinative codes generate the dynamic codes of the region, which are understood as their derivatives. They have a high probability of occurrence, higher speed of development and distribution, internal forces that make possible the self-development of the region. The scientific contribution is the substantiation of the basic code of the regional neo-industrial development. It represents the evolutionary accumulation of the rapid changes of its innovative, informational, value-based and competence-based codes stimulating the generation and implementation of new ideas regarding to economic entities adapted to the historical and cultural conditions. The article presents the code model of neo-industrial development of the region described by formulas. We applied the system analysis methods, historical and civilization approaches, evolutionary and institutional theory, economic and mathematical methods. Moreover, in the article, the authors presented the findings for the period 2011-2016 reflecting the empirical estimation of the importance of informational, institutional, innovative, value-based and competence-based codes. We made this estimation through the survey of population, representatives of business and authorities, students, as well as the professors of the leading universities of the Ural Federal District. The focus of the recommendations for the region is the acceleration of the transition to the new type of industrial development. The research results can be used when developing the programmes and projects of neo- and reindustrialization at both federal and regional levels.